Efektivitas Latihan Mobility Terhadap Peningkatan Fungsi Gerak Penyandang Disabilitas Autisme Di Share Fit - Zidan Syarif Nugraha; Kunjung Ashadi; Abdul Hafidz; Fifit Yeti Wulandari (CV. SINAR HOWUHOWU, 2026)
This study aimed to determine the effect of a mobility exercise program on improving the functional movement of individuals with autism disabilities. This research used a quantitative method with a pre-experimental design through a one-group pretest–posttest approach. The research subjects consisted of four individuals with autism aged 18–25 years who participated in a training program at the Share Fit inclusive fitness center. The instrument used in this study was the Functional Movement Screen (FMS), which consists of seven movement components: deep squat, hurdle step, inline lunge, shoulder mobility, active straight leg raise, trunk stability push-up, and rotary stability. The mobility training program was conducted for 8 weeks with a frequency of three sessions per week. Data analysis techniques included the Shapiro–Wilk normality test and the paired sample t-test for hypothesis testing. The results showed an increase in scores in most FMS components after the mobility training intervention. The statistical test results indicated a significance value (p < 0.05), meaning there was a significant difference between the pre-test and post-test scores. Therefore, it can be concluded that mobility exercises have a significant effect on improving the functional movement of individuals with autism disabilities. This study recommends the use of mobility exercises as part of an adaptive sports training program to improve movement quality and physical fitness in individuals with disabilities.